The Overshot Gate as a Flow-Measuring Device - Qasim, Jihan M. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2023)
The overshot gate is a commonly used adjustable overflow weir for regulating the upstream water level in open channels. The amount of gate movement is proportional to the water level change. However, to effectively manage the water flow, it is also important for operators to accurately measure the flow rate in the channel. This study examines an overshot gate installed at the end of a laboratory flume to estimate the flow rate under various free flow conditions. This study investigates different gate angles ranging from 9.6° to 90° to evaluate their impact on the flow properties and the discharge coefficient. The analysis of the results indicates that the maximum flow rate values can be achieved with gate inclinations from 15.5° to 47.2° with relatively lower head; the inclined alignment of the gate decreases the effective gate height which consequently increases the gate efficiency. The use of the overshot gate is advantageous over the normal gate when channel depth is limited and higher discharge is required at relatively lower head. In this study, at the highest gate inclinations, the water surface is significantly stable having the lowest values of the approach Froude number. In addition, the head to gate height ratio decreases with raising the gate due to the reduced vertical contraction of the channel. Finally, this paper proposes an empirical equation for estimating the discharge coefficient based on the gate inclination, which demonstrates good accuracy in the specified range.